Proceedings of the URECA@NTU 2011-2012 - Students of URECA Programme (2016)
Proceedings of the URECA@NTU 2011-12 is a compilation of selected URECA and FYP-URECA research papers, submitted by the URECA students of 2011-12, and under the supervision of their respective URECA professors.